Pengambilan Keputusan Strategi Pemasaran Terbaik pada PT. Astra International TBK. UD Truck SO Cabang Semarang - Hernanti, Sania Bunga Pradani; Waluyo, Dwi Eko; Izzhati, Dwi Nurul (Universitas Dian Nuswantoro, 2017)
The sale of UD Truck Quester unit at PT Astra International UD Truck SO Semarang branch does not show any improvement in 2015. This condition even tends to stagnate. Not achieving the target that has been set is an indication that the marketing strategy that is used today has not given optimal results. Therefore, the need for a new marketing strategy that can drive sales in PT Astra International UD Truck SO Semarang branch. Nevertheless, of course the marketing strategy developed will be very diverse and needs to be chosen well so as to give the best results. For this reason we use the Analytical Network Process (ANP) method and also TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) to select the best marketing strategy in choosing the best marketing strategy. The result of this research got the conclusion that best strategy chosen for PT. Astra International UD Truck SO Semarang Branch is a segmentation based on the ideal solution of negative and positive